Correlation between basal serum IGF-1 levels and functional autonomy in elderly women. (Correlación entre los niveles sericos de IGF-1 basal y autonomía funcional en las ancianas.) - Rodrigo Gomes de Souza Vale; Rosana Dias de Oliveira; Carlos Soares Pernambuco; Yúla Pires da Silveira Fontenele de Meneses; Jefferson da Silva Novaes; Armèle de Fátima Dornelas de Andrade (Ramón Cantó Alcaraz, 2009)
Abstract The aim of the present study was to determine the degree of correlation between basal serum IGF-1 levels and functional autonomy in the performance of activities of daily living (ADL). The sample comprised 11 elderly individuals, disregarding their ADLs (age = 68.18 ± 5.19 years; body mass index (BMI) = 28.89 ± 3.44 kg/m2) and not enrolled in physical exercise programs for at least 3 months. The subjects were submitted to a battery of 5 functional autonomy tests from the GDLAM protocol and blood collection to assess serum IGF-1 levels. Using Pearson’s correlation, we found a significant mean correlation coefficient (r) between the 10 m walking test (10mW) and IGF-1 (r = -0.690; p = 0.009) and mean correlation, but not significant between the putting on and removing a t-shirt test (PRTS) and IGF-1 (r = -0.528) and between the general autonomy index (AI) and IGF-1 (r = -0.417). The correlation was low in the remaining tests, but inversed. This suggests that the decline in IGF-1 with age may decrease ADL performance in the elderly. Key words: Serum IGF-1; ADL; elderly. Resumen El objetivo del presente estudio fue comprobar el nivel de la correlación entre los niveles de serum basal de IGF-1 y la autonomía funcional para la realización de las actividades de la vida diaria en personas mayores (edad = 68,18 ± 5,19 años; índice de la masa corporal, IMC = 28,89 ± 3,44 kg/m2), no participantes de los programas de ejercicios físico desde hace un mínimo de 3 meses. Los sujetos fueron sometidos a una batería de 5 tareas de autonomía funcional del protocolo GDLAM y un análisis de sangre para evaluar los niveles de serum de IGF-1. A través de la correlación de Pearson se comprobó la existencia de un coeficiente de la correlación (r) medio y significativo entre el examen de la marcha 10m (C10m) y el IGF-1 (r = -0,690; p=0,009) y la correlación media, pero no significativa ,entre el test de vestirse y quitarse una camiseta (VTC) y el IGF-1 (r= -0,528), y entre el indice general de la autonomía (IG) y el IGF-1 (r= -0,417). En los demás test la correlación fue baja, e inversa. Estos resultados sugieren que el descenso del IGF-1 con el envejecimiento puede disminuir el desempeño en las AVD de las personas mayores. Palabras clave: Serum IGF-1; Actividades de la vida cotidiana; personas mayores.